CHANGES OF PELVIC FLOOR MUSCLE FUNCTION DURING PREGNANCY - Márta HOCK; Péter TARDI; Eszter AMBRUS; Anett TÓVÁRI; Brigitta HAJNAL; Brigitta SZILÁGYI; Eleonora LEIDECKER; Bálint MOLICS; Melinda JÁROMI; János KRÁNICZ; József BÓDIS; Pongrác ÁCS (Cluj University Press, 2019)
Objective: It is known, that incontinence rarely develops during pregnancy. The authors examined pelvic floor muscle function changes during pregnancy. Study Design: Authors examined 156 women and performed vaginal squeeze pressure measurements. Statistical data were analyzed by t-test, differences were considered to be significant at p<0.05. Results: Significant difference was found concerning maximum voluntary contraction (p=0.002) and duration of maximum muscle contraction (p=0.012) in young nulliparous women compared to average results of pregnant women. This result can be proved in young nulliparous women and among pregnant women in the 2nd (p=0.045), and 3rd trimesters (p=0.005). Comparing only the results of pregnant women a significantly decreased pelvic floor muscle strength was observed (p=0.032) in women exercising occasionally. Significantly weaker muscle strength was demonstrated in those young nulliparous women (n=21) who experienced vaginal wind (p=0.003) than in young nulliparous women without symptoms. Conclusions: Vaginal contraction strength decreases during pregnancy.